Pengaruh Persepsi Konsumen, Social Media Marketing, Dan Electronic Word Of Mouth Terhadap Minat Beli Pada Perusahaan Jasa PT. JNE Kraksaan - Sah, Imam Alfin; Hermanto, Hermanto; Andrianata, Mufid (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted at PT JNE which is located in Kraksaan District, Probolinggo Regency, the aim is to find out whether there is an influence of consumer perceptions, social media marketing, and electronic word of mouth on buying interest in the service company PT JNE Kraksaan. A sample of 105 respondents in this study, selected through a nonprobability sample purposive sampling approach. This research data collection was carried out by distributing questionnaires to selected respondents. This study uses quantitative research associative approach, with data analysis using SPSS version 26 which consists of validity test, reliability test, classical assumption test, coefficient of determination, and hypothesis testing. The methodology in this study is multiple linear regression analysis techniques. The findings in the study indicate that there are variables of consumer perception, social media marketing, and electronic word of mouth that have a significant influence on the purchase intention of PT JNE Kraksaan.